A N'Dama cattle resource population for research on trypanotolerance - Wissocq, N.M.; Monsengo, B.; D'Ieteren, G.D.M.; Mommens, G. (OAU/STRC, 2001)
The genetic components of trypanotolerance measurements must be determined in well controlled on going production systems where the necessary identification and/or quantification of environment and genetic effects are possible. A resource population has been established in the Mushie District Bandundu Province, Democratic Republic of Congo, within a commercial ranch situated in one of the highest available tsetse/trypanosomosis challenge areas having cattle. Cattle are grade N'Dama selected from an original group imported into R.D. Congo 75 years ago. Breeding cows are maintained in multi-sire herds. Parentage (sire) determination in the experimental population is done through molecular genetic markers (micro-satellites). In order to evaluate the genetic diversity within the experimental population, 50 unrelated bulls were genotyped for 33 bovine microsatellites, mapping 19 chromosomes. It was concluded that the variability of and polymorphism of, the markers in the resource population is substantial and will allow accurate parentage determination. More importantly for the relevance of the research on the within-breed genetic variation of trypanotolerance measurements, it was concluded that the resource population was one of the purest N'Dama cattle population available for research, exposed to high level of natural trypanosomosis risk, as indicated by the likely absence of introgression of Zebu type genes.